2010
DOI: 10.1002/ijc.25073
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antibodies induced by a conjugate vaccine on 4‐(methylnitrosamino)‐1‐(3‐pyridyl)‐1‐butanone absorptive transport, metabolism, and proliferation of human lung cells

Abstract: One of the most abundant and potent lung carcinogen is the nicotine-derived tobacco-specific nitrosamine, 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK). The monoclonal antibody P9D5 induced with a NNK-conjugate vaccine was used to investigate the ability of NNK-specific antibodies to modulate NNK-induced adverse effects as well as its absorptive transport and metabolism in two lung cancer cell lines . Transport experiments in Calu-3 cells with a 50-fold molar excess of apical P9D5 increased the recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…Previous studies using monoclonal antibodies have mitigated the acute toxicity effects of drugs such as cocaine, heroin, methamphetamine, colchicine, oleander and other related substances [37,38,39,40]. Others have ameliorated the chronic toxicity associated with chemicals such as PCP, NNK and nicotine [17,41,42,43]. The current work builds upon these studies by creating a high affinity recombinant anti-NNK binding site derived from a mouse monoclonal antibody specific for NNK.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using monoclonal antibodies have mitigated the acute toxicity effects of drugs such as cocaine, heroin, methamphetamine, colchicine, oleander and other related substances [37,38,39,40]. Others have ameliorated the chronic toxicity associated with chemicals such as PCP, NNK and nicotine [17,41,42,43]. The current work builds upon these studies by creating a high affinity recombinant anti-NNK binding site derived from a mouse monoclonal antibody specific for NNK.…”
Section: Discussionmentioning
confidence: 99%
“…26 Our earlier work demonstrated that antibodies derived against low molecular weight carcinogens protect cells in vitro by a number of expected and unexpected mechanisms against adverse effects of carcinogens. 12,[23][24][25] We demonstrated in a bicompartment model of polarized intestinal cells (Caco-2) that antibodies have the potential to reduce the absorptive transport. 23 The biological relevance of antibodies was shown by modulating the B[a]P metabolism and DNA adduct formation in vitro.…”
Section: Benzo[a]pyrene (B[a]pmentioning
confidence: 99%
“…12,13 Hapten-specific antibodies against biologically active low molecular weight compounds have been widely applied as therapeutic agents to reverse their pharmacological effects, [14][15][16][17][18][19][20][21][22] but their use as immunoprophylactic agents has only recently gained some interest. 12,[23][24][25][26][27][28][29] Several candidate vaccines against nicotine and cotinine, its major metabolite, have been developed and are in clinical trials. 14,22,[30][31][32][33] We have developed an experimental vaccine based on B[a]P conjugated to tetanus toxoid (TT) or diphtheria toxoid (DT) as carrier proteins, that induces high levels of antibodies against this carcinogen.…”
Section: Benzo[a]pyrene (B[a]pmentioning
confidence: 99%
“…Mucosal Abs inhibited the transport of Cg into and through respiratory and intestinal epithelium in vivo (Moolten et al, 1978a, Silbart and Keren, 1989, Rasmussen and Silbart, 1998), as well as mucosal-like monoclonal Abs in the model experiments in vitro with dialysis membrane (Silbart et al, 1996) or epithelium cell monolayers (De Buck et al, 2005, De Buck et al, 2010). The monoclonal mucosal-like Abs reduced the amount of Cg genotoxic metabolites and inhibited the Cg-induced cells proliferation in vitro (De Buck et al, 2005, De Buck et al, 2010). In contrast serum-like model Abs increased the penetration of Cg through membrane or cell monolayers and its metabolic activation (Silbart et al, 1996, De Buck et al, 2005).…”
Section: Antibodies Against Chemical Carcinogens and Steroidsmentioning
confidence: 99%